2007
DOI: 10.1002/chin.200704266
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Prognosis of Overt Disseminated Intravascular Coagulation in a General Hospital: Meaning of the ISTH Score System, Fibrin Monomers, and Lipoprotein‐C Reactive Protein Complex Formation

Abstract: The meaning, the utility, and the prognostic significance of the International Society of Thrombosis and Hemostasis overt disseminated intravascular coagulation (DIC) score and other parameters of coagulation activation including soluble fibrin monomer complexes (SFMC), antithrombin and protein C consumption, and formation of lipoprotein-C-reactive protein (LP-CRP) complexes (MDA slope 1 and flag A2) were evaluated in 165 inpatients from a general hospital for whom DIC testing was required by the attending phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
1
10
1
1
Order By: Relevance
“…Previous studies have proposed that, in addition to ADAMTS‐13 activity, the levels of AT‐III, SF, Fib, HMGB1, protein C, TM, and PIC can help predict the prognosis of DIC without rTM treatment [24–30]. Although most of those coagulation markers were also abnormal before treatment in our series, they were not predictive of the outcome for DIC treated with rTM.…”
Section: Changes In Biomarkers On Daycontrasting
confidence: 53%
“…Previous studies have proposed that, in addition to ADAMTS‐13 activity, the levels of AT‐III, SF, Fib, HMGB1, protein C, TM, and PIC can help predict the prognosis of DIC without rTM treatment [24–30]. Although most of those coagulation markers were also abnormal before treatment in our series, they were not predictive of the outcome for DIC treated with rTM.…”
Section: Changes In Biomarkers On Daycontrasting
confidence: 53%
“…Increasing scores strongly correlated with mortality. Others have similarly confirmed this independent prediction of mortality by the ISTH DIC score and its added prognostic value to the Acute Physiology and Chronic Health Evaluation (APACHE) II system [7][8][9].…”
Section: Resultsmentioning
confidence: 75%
“…A strong correlation between an increasing DIC score and mortality has been demonstrated by several studies, For each DIC point, increases in the odds of mortality of 1·25–1·29 have been demonstrated (Bakhtiari et al , 2004). Several other studies have similarly confirmed that the presence of overt DIC by the ISTH algorithm is independently predictive of mortality (Gando et al , 2005; Sivula et al , 2005; Cauchie et al , 2006). These studies show that patients with sepsis and DIC, according to the scoring system, have a significantly higher mortality of 43%, as compared with 27% in patients without DIC.…”
Section: Diagnosis Of Dicmentioning
confidence: 63%